Future buildings as carbon sinks: Comparative analysis of timber-based building typologies regarding their carbon emissions and storage - Dzhurko, Daria; Haacke, Ben; Haberbosch, Asta; Köhne, Linde; König, Nora; Lode, Frida; Marx, Antonia; Mühlnickel, Luka; Neunzig, Nina; Niemann, Annika; Polewka, Henrieke; Schmidtke, Lea; et al. (Frontiers in Built Environment, 2024)
The building and construction sector is responsible for a large share of carbon emissions resulting in the need to reduce them to mitigate climate change. Timber construction methods promise to lower emissions combined with biogenic carbon storage in the built environment. While there are several studies comparing the emissions of mineral-based and timber-based buildings, a consistent comparison of different timber-based building assemblies is still missing. This study compares carbon emissions from material production and carbon storage capabilities of four timber-based and two brick and reinforced concrete building assemblies. These assemblies were designed for a residential multi-storey building in Berlin, Germany. To compare and rank the carbon impacts of these assemblies we introduce a carbon storageto-emission ratio. The calculations were performed using a Carbon Cycle Assessment Model implementation in Python. The results indicate an average reduction in carbon emissions of timber-based building assemblies by 32.68 % to "Brick" and 47.640.4 % to "Reinforced Concrete", respectively. Across the timber-based building assemblies, the carbon emissions range between 85 t and 115 t, leading to an average of 105 t per building. Pronounced differences were observed in carbon storage, with the "Dowel Laminated Timber" building assembly storing more than three times the amount of carbon compared to "Light Weight Timber" assembly. To further reduce emissions from buildings and the construction sector and potentially enhance urban carbon storage, "Cross Laminated TimberGlue Laminated Timber" and "Dowel Laminated Timber" building assemblies were identified as the most promising.